Study guides

Q: How do you solve 3 step equations with parentheses?

Write your answer...

Submit

Related questions

3*-7=29

Parentheses are the following symbols: ( & ). These are parentheses. These help to do equations for example : 3+2x3=9 u are to put the parentheses or the backetts or the {} to help solve the equation so this is the way to put them in : 3+(2x3)=9. Hope This Helps!

Well, that's one method to solve the quadratic equation. Here is an example (using the symbol "^" for power): solve x^2 - 5x + 6 = 0 Step 1: Convert the equation to a form in which the right side is equal to zero. (Already done in this example.) Step 2: Factor the left side. In this case, (x - 3) (x - 2) = 0 Step 3: Use the fact that if a product is zero, at least one of its factors must be zero. This lets you convert the equation to two equations; x - 3 = 0 OR x - 2 = 0 Step 4: Solve each of the two equations.

Step one is by expressing one of the equation into one term that is taking one unknown in the form of other. Step two is replacing the unknown into equation 2. Step 3 is replacing the found unknown into one of initial equations to find the other unknown.

You can solve the system of equations with three variables using the substitute method, or using matrix operations.

algebraic equations that require 2 or more steps to solve. ex: 3(x - 2) = x + 8

If you already know that x = -3 and y = 5 what linear equations are you wanting to solve?

18=3(3x-6)

They change the order of operations by giving priority to the contents of the parentheses. For example...2 + 3 x 4 = 14but...(2 + 3) x 4 = 20

If the problem is written symbolically with no parentheses, 2 / 3 * 7, then since division and multiplication have the same priority, you simply solve it left-to-right, and the answer is 14/3 or 4 2/3.

You multiply one or both equations by some constant (especially chosen for the next step), and add the two resulting equations together. Here is an example: (1) 5x + 2y = 7 (2) 2x + y = 3 Multiply equation (2) by -2; this factor was chosen to eliminate "y" from the resulting equations: (1) 5x + 2y = 7 (2) -2x -2y = -6 Add the two equations together: 3x = 1 Solve this for "x", then replace the result in any of the two original equations to solve for "y".

3+3=6 add get answer who asks these things!

Well step 1 centres step 2 edge pairs step 3 solve as 3x3 so 3 but you could say 8

Solve: 3(x+1) = 2(x-8) + 3 First, remove the parentheses by distributing (multiplying out the numbers): 3x + 3 = 2x - 16 + 3 Then, combine any like terms on the same side of the equals sign; 3x + 3 = 2x -13 Then, move the like terms on opposite sides of the equals sign to the same side of the equals sign (don't forget to change the signs). 3x -2x = -13 - 3 Then combine the like terms on the same side of the equals sign again. x = -16 The last step is always to check the answer to make sure the it is correct. So, start with the original equation, but substitute in the value for x that we just found: 3(x+1) = 2(x-8) + 3 3(-16+1) = 2(-16-8) + 3 3(-15) = 2(-24) + 3 -45 = -45 So the answer is correct!

Ask you math professor

To solve for 3 unknown variables you need 3 independent equations. You have only 1.

If you know matrix algebra, the process is simply to find the inverse for the matrix of coefficients and apply that to the vector of answers. If you don't: You solve these in the same way as you would solve a pair of simultaneous linear equations in two unknowns - either by substitution or elimination. For example, change the subject of one of the equations to express one of the variables in terms of the other two. Substitute this value into the other two equations. When simplified, you will have two linear equations in two variables.

It depends on the particular equation, of course. You can use several tricks, including eliminating things outside the parentheses, and using the distributive property. Here is one example: 2(x+3) = 10 Divide both sides by 2: x + 3 = 5. (The remainder should be easy to solve. Another soution, using the distributive property: 2(x+3) = 10 2x + 6 = 10 Again, I am assuming you know how to solve equations WITHOUT parentheses, so I won't give the full solution here.

One out of many examples of two step equations that equal 29 is: (9 x 3) + 2

(a + b)3 = a3 + 3a2b + 3ab2 + b3

As for example if 9x = 27 then x = 3

3(2x-4)=2(4x+3)

y = 6x - 11 -2x - 3 y = -7

First you subtract 7 from 4 because it's in parentheses. Then you multiply the difference by 3 because multiplication/division is done before addition/subtraction (unless the addition/subtraction is in parentheses). Then subtract 11 from the product. It's negative twenty.

(x+y) is the same as x+y 3(x+y) is 3 times as much. You multiply both x and y with 3 = 3x+3y 3(2x+4y) is the same as 3*2x+3*4y = 6x+12y This is the general start of how to "solve" and do calculations with parentheses. I am sure other people can add more examples with higher difficulty Regards.